Islam in India's transition to modernity - Karandikar, Maheshwar A. (Bombay : Orient Longmans, 1968)
In a scholarly critique of Islamic thought up to modern times, the author probes the nature of the religious, social, and political conflicts between Muslim and Hindu, and opens the way for the formulation of new attitudes and politics by both the Muslims and the Indian government.
includes bibliographical and index
Keywords: Muslims -- India